(untitled) - O'Brien, Mary Barmeyer (Guilford, Connecticut, 2016)
Recounts the life of the Montana representative who was the first congresswoman and a dedicated pacifist who voted against both world wars.
Keywords: Nhà lập pháp nữ,Women legislators; Tiểu sử,Biography; Hoa Kỳ,United States